English Language Teaching: an analysis of the implementation of ludic strategies with 7th graders at Simón Bolivar School in Zarzal, Valle del Cauca. (2017)
The present research project shows the results of an action research type, which contains a mixed approach research focused on the application of ludic strategies in English classes of 7th graders from the public high school Simon Bolivar in Zarzal, Valle. In this research it were implemented pre and post surveys, interviews and observations to collect quantitative and qualitative data from the students and the main English teacher. An intervention is applied to observe how students react while the implementation of ludic strategies in their English classes. Thus, it is concluded the benefits of the application of ludic activities and the activities than optimizes time.